(NtRENIE W PRIRODE I TEHNIKE (B/s - (NlISOWSKIJ(B, (Nl(B.(Np(B.s; (NsALOMONOWI^(B, (Na(B.(Ne(B.s; (NhAJKINA(B, (Ns(B.(N|(B.s ((NmOSKWAs (NlENINGRAD (B:s (Nogiz(B. (NgOSTEHIZDAT(B,s, 1948)
(NzAKL(B.: (NS(B. 52s
Keywords: (NtRENIEs